The Wiley-Blackwell handbook of addiction psychopharmacology - MacKillop, James, 1975-; De Wit, Harriet (Chichester, West Sussex ; Malden, Mass. : Wiley-Blackwell, 2013)
"The Wiley-Blackwell Handbook of Addiction Psychopharmacology is an authoritative collection of the most current research approaches to the study of drug addiction. Provides students and scholars with the practical tools to do the best work possible in addiction psychopharmacology Features reviews on the empirical relevance of the research methods and the nuances of the methodologies used Topics covered include core methods for assessing drug effects, distal and proximal determinants of drug use, and insights from cognitive neuroscience Includes contributions from a diverse range of experts that reflect the multidisciplinary nature of the field"--
pt. I. Distal determinants of drug use -- pt. II. Proximal determinants of drug use -- pt. III. Insights from cognitive science.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Substance abuse -- Chemotherapy -- Handbooks, manuals, etc; Psychopharmacology -- Handbooks, manuals, etc; Electronic books